Effect of Duty Cycle Control on Performance of Sepic DC – DC Buck-Boost Converter under Resistive Load Applications (Lafia Journal of Scientific and Industrial Research, 2025)
This paper investigates the effect of duty cycle control on the performance of the SEPIC (Single-Ended Primary Inductor Converter) DC–DC buck-boost converter, particularly when subjected to resistive load applications. The SEPIC converter, known for its ability to output a voltage either greater or lesser than the input, finds broad application in power supplies and renewable energy systems. An analysis of how the duty cycle influences key performance metrics—such as output voltage, currents and voltage ripple is presented. Simulation result demonstrate that careful modulation of the duty cycle enables optimization of converter performance, offering valuable insights into how these converters can be tuned to enhance efficiency in resistive load scenarios. The results obtained reveal that the Sepic dc dc converter is capable of delivering a maximum output power approximately 1857W at duty cycle of 80 % with 20 kHz switching frequency. Also, at the same switching frequency, 20 % duty cycle, a minimum output power of approximately 5.34 W was obtained. These insights are valuable for power electronics engineers seeking to optimize SEPIC converters for domestic load applications.